ANALISIS PENGARUH STRATEGI PROMOSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA RUMAH MAKAN SAUNG WULAN - Eka Giovana Asti; Eka Avianti Ayuningtyas (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2019)
Culinary business which includes businesses such as restaurants, cafes, and food stalls shows that the business sector is experiencing positive growth. So also happened in the area of West Java Province in particular, the growth in the number of restaurants, cafés and food stalls also shows that the rate of growth is rapid. This indicates the competition in that business sector is also getting tougher. To overcome the increasingly fierce competition, an effort is needed to overcome that thing and strive to prioritize to the consumers. One effort that can be done by business people is to create a consumer-oriented marketing strategy. This research will analyze two factors that are thought to influence consumer loyalty, namely Promotion Strategy and Service Quality Strategies.Based on the results of the calculation of the correlation coefficient between the Promotion Strategy and Service Quality together on Consumer Loyalty in Saung Wulan Restaurant Entrepreneurs, is positive with a very strong level of relationship that is equal to 0.866 and after being tested by hypothesis with the F test the correlation has a significant relationship.Then the regression coefficient test results also showed a straight and positive relationship seen from the contribution of Promotion Strategy and Service Quality variables to Consumer Loyalty in Saung Wulan Restaurant Entrepreneurs, which is equal to: Y = 22,562 + 0,702X1 + 1,551 X2. Keywords:Promotion Strategy, Service Quality and Consumer Loyalty